Integrative GWAS and transcriptomic analyses reveal regulatory genes controlling shoot branching in sunflower - Sun, Yiyi; Wang, Yanwen; Bai, Jingyan; Guo, Jiatong; Li, Guiting; Yang, Xiaojie; Tian, Qiuzhen; Huang, Yingying; Lv, Shuping; Cao, Hengchun; Liu, Lingyun (Frontiers in Plant Science, 2025)
Shoot branching plays a crucial role in shaping plant architecture, influencing both yield potential and ornamental qualities in sunflower (Helianthus annuus L.), but the genetic mechanisms underlying this trait are still not well understood. To investigate this, we performed a genome-wide association study (GWAS) using 82 sunflower accessions with diverse branching phenotypes and identified 62 significant single-nucleotide polymorphisms (SNPs). Of these, sixty SNPs clustered within a 12.40–17.13 Mb region on chromosome 10. Linkage disequilibrium (LD) block analysis delineated this region, containing 113 genes. Integration of transcriptomic analysis of shoot apical meristems of both branched and unbranched lines revealed 12 differentially expressed genes (DEGs) within the GWAS interval, including two long non-coding RNAs (lncRNAs) that demonstrated significant co-expression with several protein-coding candidates. Notably, one gene (HanXRQr2_Chr10g0423211) harbored a nonsynonymous SNP and displayed moderate differences in expression. Tissue-specific RNA-seq and qRT-PCR confirmed the involvement of these 13 genes in branching regulation. Overall, this study advances our understanding of the genetic mechanisms controlling shoot branching in sunflower and highlights candidate genes for targeted breeding to enhance plant architecture.